Program naprawczy samorządowego samodzielnego publicznego zakładu opieki zdrowotnej .......... 89 - Delfina Klisowska, Izabela (Samorząd terytorialny na Dolnym Śląsku: Sprawy, dylematy i wyzwania, 2025)
A RECOVERY PROGRAMME FOR AN INDEPENDENT PUBLIC HEALTHCARE INSTITUTION ESTABLISHEDBY LOCAL GOVERNMENTLocal government units, as founding bodies of independent public healthcare institutions, hold statutory responsibilities and powers in recovery processes, particularly concerning financial performance. Recovery programmes were designed as tools for effective supervision over these entities. Nearly a decade has passed since the introduction of recovery programmes in 2016. However, the financial condition of these institutions has not significantly improved, particularly due to legislative changes that increased operational burdens. The significance of recovery programmes increased following the Constitutional Tribunal’s ruling of 20 November 2019, especially in relation to institutional competences and systemic influence.